TOOLS FOR COURSE PREPARATION IN METRIC COMPETENCE FORMAT - Galimyanov, Anis; Talal, Nijes (Revista Inclusiones, 2019)
Currently, the determination of the quality of training is the most important task. In our work, we use the definition of quality monitoring according to ABC-abilities, which are defined by N.K.Nuriyev and L.N. Zhurbenko. According to them, competence in any field is invariantly supported by the triad of abilities <A, B, C> of a certain level of development, i.e. ABC abilities and knowledge, as auxiliary means, where A, B, C are formalization, constructive and performing abilities, respectively. The course editor in the form of a written application is developed in the form of a web-based student training program that allows to evaluate and visualize the level of ABC - a student's abilities. Based on these results, a decision is made on the trajectory of further education.